1982
DOI: 10.1128/aem.43.3.603-608.1982
|View full text |Cite
|
Sign up to set email alerts
|

Ozone inactivation of cell-associated viruses

Abstract: The inactivation of HEp-2 cell-associated poliovirus (Sabin 1) and coxsackievirus A9 was investigated in three experimental systems, using ozone as a disinfectant. The cell-associated viral samples were adjusted to a turbidity of 5 nephelometric turbidity units. The cell-associated poliovirus and coxsackievirus samples demonstrated survival in a continuous-flow ozonation system at applied ozone dosages of 4.06 and 4.68 mg/liter, respectively, for 30 s. Unassociated viral controls were inactivated by the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Ozone residuals of 4.70 and 5.45 mg/L were measured after a 2‐min treatment. In this study cell‐associated enteric viruses were protected from inactivation by exposure to ozone (Emerson and others 1982), which suggests that food matrices may also have a protective effect.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Ozone residuals of 4.70 and 5.45 mg/L were measured after a 2‐min treatment. In this study cell‐associated enteric viruses were protected from inactivation by exposure to ozone (Emerson and others 1982), which suggests that food matrices may also have a protective effect.…”
mentioning
confidence: 64%
“…The presence of organic substances can neutralize the ozone needed to inactivate microoganisms when mixed with cells, cellular debris, food, or feces. Emerson and others (1982) studied the disinfection potential of ozone on human epithelial cells (HEp‐2) infected with poliovirus (Sabian type 1) and coxsackievirus A9 to simulate organic compounds of cells sloughed from the intestinal tract. Poliovirus unassociated with cells were completely inactivated at 0.28 mg/L of ozone in 10 s and coxsackievirus unassociated with cells were completely inactivated at 0.081 mg/L in 10 s. Alternatively, cell‐associated poliovirus was completely inactivated after a 2‐min contact time with much higher initial ozone concentrations of 6.82 and 6.50 mg/L.…”
mentioning
confidence: 99%
“…Echerichia coli, Pseudomonas aeruginosa and Serratia marcescens , as well as Candida albicans (ozone concentration necessary for elimination 0.05–0.7 µg ml −1 ) are more susceptible than staphylococcae (3–5 µg ml −1 ) (22). Ozone concentrations over 5 µg ml −1 will eliminate all microorganisms (23) in a few seconds. The irrigation of avulsed teeth with ozonized water could, hence, not only decontaminate the root surface, but also may have a positive effect on the cementoblasts in the remaining PDL adhering to the root surface.…”
mentioning
confidence: 99%
“…Ozone inactivates many viruses directly. Norwalk, collophage MS3, hepatitis A, and poliovirus are dependent on reduced sulfhydryl groups [13][14][15][16][17][18]. "Reflecting on the reduction of "critical" disulfide bonds for vaccinia virus' cellular entry, Ryser found that protein disulfide isomerase inhibitors limited HIV-1 entry into T cells [19].…”
Section: Viral Vulnerabilitymentioning
confidence: 99%